Endovascular stenting of medically refractory intracranial arterial stenotic (ICAS) disease (clinical and sonographic study) - Ayman Mohamed Nassef (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2020)
Abstract Background Atherosclerotic intracranial arterial stenosis (ICAS) is one of the most common causes of stroke worldwide and is associated with a high risk of recurrent stroke. Patients with a recent transient ischemic attack (TIA) or stroke and severe stenosis (70 to 99% of the diameter of a major intracranial artery) are at particularly high risk for recurrent stroke in the territory of the stenotic artery (approximately 23% at 1 year) despite medical treatment. Therefore, alternative therapies are urgently needed for these patients. Objective To determine the efficacy and safety of angioplasty with stenting in medically refractory ICAS and to compare its effectiveness with optimal medical treatment. Subjects and methods Fifty patients with symptomatic ICAS despite medical treatment (i.e, recurrent stroke or TIA) were enrolled and equally randomized in a prospective study where twenty-five patients underwent angioplasty with stenting and twenty-five patients received optimal medical treatment. Clinical assessment with NIHSS and mRS were done at 0, 3, and 6 months, and transracial Doppler (TCD) assessment of ICAS was done at 0 and 3 months after treatment. Results The interventional group had a better clinical outcome with mean NIHSS scores (5.2 ± 4.2, 4.43 ± 4.28 and 3.9 ± 4.7) at baseline, 3 and 6 months, respectively, in comparison to the medical group with mean NIHSS (4.5 ± 4.2, 11.42 ± 6.3, and 8.5 ± 5.1) and better functional outcome with mean mRS scores (1.3 ± 0.96, 1.2 ± 1.13, and 1.0 ± 1.13) at baseline, 3 and 6 months, respectively, in comparison to the medical group (0.84 ± 0.75, 2.28 ± 1.2, and 2 ± 1.24). TCD assessment of ICAS showed a marked reduction of the percentage of stenosis on 3 months of follow-up among the interventional groups (only 5.6% had > 70% stenosis) in comparison to the medical group (85.7% had > 70% stenosis). Recurrent ischemic events on 6 months of follow-up were 16% among interventional groups in comparison to 84% among medical groups. The mortality rate was 8% among interventional groups due to subarachnoid hemorrhages (SAH) related to procedure in comparison to 28% among medical groups secondary to ischemic events. The intraoperative success rate was 96% with the failure of stent deployment in 1 patient due to the tortuous anatomy of vessels. Early post interventional complication rate, i.e, SAH was 8%. Late post interventional restenosis and occlusion rates were 8% on 3 months of follow-up. Conclusion Endovascular stenting of medically refractory ICAS is more efficacious and effective with better clinical and functional outcomes than optimal medical treatment; however, its safety is still debatable. Trial registration Done at ClinicalTrials.gov . Trial ID (NCT Number) NCT04393025 .